Redesign Tigaraksa City Forest Lake's Tourism Landscape in Tangerang Regency Using Sustainable Tourism Approach - Wistoro, Luthfie Adli; Hutriani, Ina Winiastuti; Franjaya, Eduwin Eko (Universitas Indraprasta PGRI, 2025)
Tigaraksa Urban Forest is a city forest located in the Tangerang Regency Government Center Area with an area of 8.5 hectares. Based on the Tangerang Regency RTRW 2011-2031, Tigaraksa Urban Forest is planned as a lake tourism area. And the Banten Province RIPPDA 2018-2025 has a vision of